Preliminary findings of age and male sexual characteristics and potential effect to semen characteristics and cryopreservation of the critically endangered Bornean orangutan in Malaysia. - Zainuddin, Zainal Zahari; Tarmizi, Reza; Chee, Yap Keng; Sarkawi, Nur Nabila; Ahmad, Hafandi; Salleh, Annas; Mohamad Tahir, Nur Diyana; Baiee, Falah; Che-Amat, Azlan; Fitri, Wan-Nor (Springer Science and Business Media LLC, 2022)
Bornean orangutan is a critically endangered non-human primate; however, the threat of extinction is not merely from poaching and habitat loss. Orangutan survival is also threatened by the genetic loss and genetic bottleneck due to the low effective population, prompting the dire need for an immediate genetic preservation program through systematic biobanking and assisted reproductive technology (ART). This study aims to provide integral data to the semen characteristics, extension, and cryopreservation of the Bornean orangutan and the potential relationship to male traits. Five captive orangutans from Sepilok Orangutan Rehabilitation Centre (SORC) with a mean body weight of 52.81 ± 7.00 kg were used for this study. Semen collection was performed using electroejaculation (EE) under complete general anesthesia. Semen was subjected to macroscopic and microscopic evaluation while testicular measurement was obtained using digital calipers. The semen characteristics of the orangutans are volume (778 ± 250.21 µl), pH (7.80 ± 0.25), concentration (32.38 ± 17.40 × 106 sperm/ml), total motility (61.00 ± 12.88%), adjusted motility index (48.76 ± 11.32%), live spermatozoa (77.75 ± 6.94%) and normal spermatozoa (11.48 ± 11.34%). Analysis of variance statistical analysis test was used to compare the significant difference between means, at (p < 0.05). Spermatozoa concentration was the only significant different parameter between individuals. Testes biometry parameters are statistically significant between the flanged and unflanged individuals. Live spermatozoa are different in adult and sub-adult individual while teratospermia was found to be consistently high in all individuals. Chilled and post-thaw quality after cryopreservation suggests promising survivability of spermatozoa. Semen collection with EE yields a consistent and acceptable quality of spermatozoa for cryopreservation, biobanking purposes, and potential application of ART.